“Maybe next time he’ll think before he cheats”: masculine honor beliefs and perceptions of women’s aggressive responses to men’s infidelity - Martens, Amanda Lynn (Kansas State University, 2021)
“Before He Cheats,” a popular country music song by Carrie Underwood, depicts a woman destroying her male significant other’s vehicle after discovering he has been unfaithful. Given that country music has been shown to reflect cultural values associated with the United States (e.g., Cobb, 1982), this song may indicate that women’s aggressive responses, under specific conditions, are perceived as justified, appropriate, and necessary. The focus of the current work, honor ideology stemming from an honor culture within the United States, has traditionally focused on men’s behavior and contends it is men’s aggression that is justified, appropriate, and necessary, with relatively little attention examining the relationship between women’s aggression and honor ideology. Accordingly, through three studies, the current research examined how individuals’ honor beliefs are related to their perceptions of a woman’s (i.e., wife) aggressive responses to discovering her significant other (i.e., husband) has been unfaithful. Study 1 found that increased levels of masculine honor beliefs were associated with increased positive perceptions of the wife when she responded by slapping her husband hard across the face. These results are important because they extend the honor literature and indicate that women may also be perceived positively by those higher in masculine honor beliefs, when responding to an honor-related insult or threat (e.g., infidelity) with physical aggression. However, Study 1 did not allow for directly testing the Honor Ideology Hypothesis, Gender Roles Hypothesis, and Gendered Honor Ideology Hypothesis against one another. Accordingly, the purpose of Study 2 was to examine and identify responses a woman may have in response to infidelity in a marriage that would allow for the three competing hypotheses to be tested against each other. The initial twenty-three potential responses were narrowed down such that a wife responding by punching either the husband or the other woman in the face represented the Honor Ideology Hypothesis. A wife responding by calling her friends to discuss either the other woman or the husband’s actions represented the Gender Roles Hypothesis. And finally, a wife responding by posting on social media to ruin the reputation of either the husband or the other woman represented the Gendered Honor Hypothesis. Across all of these conditions, increased levels of masculine honor beliefs were associated with increased perceptions that the wife was trustworthy, and that the wife’s responses were justified and honorable. Further, like in Study 1, as masculine honor beliefs increased, perceptions of the wife’s responses of punching in the face as necessary also increased. Although the results did not definitively support any one of the three competing hypotheses above the others, the results did indicate that women’s aggressive responses, under specific conditions, were perceived more positively (i.e., justified, appropriate, and necessary) as masculine honor beliefs increased. Thus, these results have important implications for researchers’ approach to the study of honor ideology stemming from the United States. Results suggest that researchers interested in this honor ideology now take a more multifaceted approach, as opposed to the current unidimensional approach (i.e., men’s aggression in response to insult and threat), and study specific subsets of honor ideology. Overall, by including women as the focus, and empirically testing how honor ideology is related to perceptions of a woman’s aggression, the current research is a novel and important contribution to the social psychological research on honor expression, maintenance, and ideology.
Keywords: Honor; Women's aggression